2011
DOI: 10.1111/j.1600-0463.2011.02782.x
|View full text |Cite
|
Sign up to set email alerts
|

High expression of miR-21 in tumor stroma correlates with increased cancer cell proliferation in human breast cancer

Abstract: Low-risk and high-risk breast cancer patients are stratified primarily according to their lymph node (LN) status and grading. However, some low-risk patients relapse, and some high-risk patients have a favorable clinical outcome, implying a need for better prognostic and predictive tests. Micro RNAs are often aberrantly expressed in cancer and microRNA-21 is upregulated in a variety of cancers, including breast cancer. High miR-21 levels have been associated with poor prognosis. To determine the cellular local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
49
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 42 publications
(64 reference statements)
10
49
0
Order By: Relevance
“…As an oncomir, miR-21 is upregulated in a variety of human malignancies, such as cholangiocarcinoma, breast cancer, lung cancer, colorectal cancer, and prostatic carcinoma (8)(9)(10)(11)(12). Consistent with these studies, we demonstrated that miR-21 expression was significantly higher in HCC tissues and cell lines than that in matched non-tumor tissues and normal human hepatic cells, suggesting that high miR-21 expression was tightly associated with tumor development.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…As an oncomir, miR-21 is upregulated in a variety of human malignancies, such as cholangiocarcinoma, breast cancer, lung cancer, colorectal cancer, and prostatic carcinoma (8)(9)(10)(11)(12). Consistent with these studies, we demonstrated that miR-21 expression was significantly higher in HCC tissues and cell lines than that in matched non-tumor tissues and normal human hepatic cells, suggesting that high miR-21 expression was tightly associated with tumor development.…”
Section: Discussionsupporting
confidence: 77%
“…Consistent with these studies, we demonstrated that miR-21 expression was significantly higher in HCC tissues and cell lines than that in matched non-tumor tissues and normal human hepatic cells, suggesting that high miR-21 expression was tightly associated with tumor development. Inhibition of miR-21 expression could restrain tumor growth in breast cancer cells (9), while overexpression of miR-21 could increase cell invasion in colon carcinoma (12). In this study, we observed that miR-21 expression was dramatically increased in invasive/metastatic HCC tumor tissues and tumor tissues from stage II-IV patients, as compared with that in non-invasive/non-metastatic HCC tumor tissues and tumor tissues from stage I-II patients.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…P53 protein was stabilized by HNRPK that interferes with MDM2 (Papagiannakopoulos et al, 2008). Previous studies showed no significant correlation between P53 and miR-21 (Rask et al, 2011). It is known that certain missense mutations of P53 lead to a longer half life for the protein, which its accumulation in the cells can be detected with specific antibody.…”
Section: Discussionmentioning
confidence: 99%
“…To date there are no reports on the role of miR-21 in thymocyte development or T-ALL; miR-21 has been described as an oncogene in several solid tumors. [51][52][53] Importantly, miR-21 function has been linked to cancer-related processes in hepatocellular, glioblastoma, and breast cancer. 33,[54][55][56] Furthermore, microarray analysis of miR-21 target gene expression in BM aspirates of T-ALL patients and normal controls revealed that many miR-21 targets were repressed in T-ALL patient samples, indicative of a clinical relevance of miR-21 target gene repression in T-ALL.…”
Section: Dicer1 Is Essential For Notch-driven T-all 999mentioning
confidence: 99%